Single-Element Reflective Digital Holographic Microscopy - Picazo-Bueno, José Ángel; García, Javier; Micó, Vicente (Frontiers in Physics, 2021)
Digital holographic microscopy (DHM) is a well-known microscopy technique using an interferometric architecture for quantitative phase imaging (QPI) and it has been already implemented utilizing a large number of interferometers. Among them, single-element interferometers are of particular interest due to its simplicity, stability, and low cost. Here, we present an extremely simple common-path interferometric layout based on the use of a single one-dimensional diffraction grating for both illuminating the sample in reflection and generating the digital holograms. The technique, named single-element reflective digital holographic microscopy (SER-DHM), enables QPI and topography analysis of reflective/opaque objects using a single-shot operation principle. SER-DHM is experimentally validated involving different reflective samples.